Loss of exponential stability for a thermoelastic system with memory - Alves, Bruno Ferreira; Bastos, Waldemar Donizete [UNESP]; Raposo, Carlos Alberto (My University, 2010)
In this article we study a thermoelastic system considering the linearized model proposed by Gurtin and Pipkin [8] instead of the Fourier's law for the heat flux. We use theory of semigroups [9, 11] combining Pruss' Theorem [10] and the idea developed in [5] to show that the system is not exponentially stable. © 2010 Texas State University - San Marcos.
Keywords: C0-semigroup; decay of solutions; Heat conduction with memory; Thermoelastic system